Evolution of socio-cultural policy mapping of city community design for city sociocultural space - Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Afanasieva, L. (My University, 2019)
EN: The aim of this study is to carry out a comprehensive analysis tools for mapping communities in the context of the modernization upgrade the socio-cultural space of present-day Ukrainian city. Methodology of research: To accomplish the tasks, the following general scientific and empirical methods were used such as: analysis, synthesis, comparison, systematization, generalization, as well as questionnaires, focus group research and method «World café». To analyze the development and implementation of communities mapping projects in the modern city, we are involved with axiological and activity approaches. The method of cultural mapping of the city of participatory type based on the city of Melitopol is developed. The scientific novelty of the study is an interdisciplinary correlative-integrative approach to the study of the problem of mapping, modernization and sustainable socio-cultural development of the modern Ukrainian city, which combines the cultural, philosophical and sociological principles of analysis and consists in an attempt of a culturally-analytical comprehensive study of ways of organizing the cooperation of the urban community with local self-government bodies. Conclusions. In this study, an attempt was made not only to characterize the mapping of the community as a method, but also to identify the possibilities of its use for the study of the socio-territorial space, to determine its practical significance, which, in our opinion, may serve as a scientific basis not only for knowledge, forecasting of urban socio-cultural processes, but also will contribute to the development of the communityʼs potential, the construction of the territorial organization of local self-government. UK: Метою даного дослідження є здійснення комплексного аналізу інструментів картування громад в контексті модернізаційного оновлення соціально-культурного простору сучасного українського міста. Методологія дослідження: для реалізації поставлених завдань були застосовані такі загальнонаукові та емпіричні методи, як: аналіз, синтез, порівняння, систематизація, узагальнення, а також анкетування, фокус-групове дослідження та метод «World café». Для аналізу розробок і втілення проектів картування громад сучасного міста нами задіяний аксіологічний і діяльнісний підходи. Розроблено методику культурного картування міста партисипативного типу на основі м. Мелітополь. Науковою новизною дослідження є міждисциплінарний корелятивно-інтегративний підхід до вивчення проблеми картування, модернізації та сталого соціокультурного розвитку сучасного українського міста, що поєднує культурологічний, філософський та соціологічний принципи аналізу й полягає у спробі культуролого-аналітичного комплексного дослідження шляхів
Еволюція розвитку соціокультурної політики міста від картування громад до проектування міського соціокультурного простору
Keywords: cultural mapping; participatory management; socio-cultural space of the city; cultural community; design of urban socio-cultural space